Consumer Judgment on the Practice of Greenwashing: Scale Development and Validation - Tais Pasquotto Andreoli; Esdras da Silva Costa; Leandro Campi Prearo (BBR: Brazilian Business Review)
This study aimed to develop and validate a scale to measure consumer judgment about the practice of greenwashing. For this, quantitative research was adopted as methodological procedure, which was conducted through a statistical technique characterized as multivariate analysis. Thus, in a first step, theoretical studies and reports on the characterization and/or identification of greenwashing were surveyed and analyzed, which allowed for the adoption of six main dimensions that were evidenced in a common manner. From these dimensions, some assertions were elaborated and reviewed by a jury of experts, validating the data collection instrument. With this done, two sequential quantitative surveys were conducted: the first with 381 respondents, which allowed the exploratory factor analysis to be performed, and the second with 156 participants, enabling the confirmatory factor analysis to be performed using the structural equation modeling technique. As a contribution, a satisfactory final model composed of 13 assertions was obtained.